Maternal Kangaroo care education program in the neonatal intensive care unit improved mothers' perceptions, knowledge, perceived barriers and stress relates to premature infant - Sharmiza, Samsudin; Chui, Ping Lei; Azanna, Ahmad Kamar; Khatijah Lim, Abdullah * (Wiley Open Access, 2023)
Aim: To assess the effectiveness of the maternal kangaroo care education programme over 1 month and 3 months on the mother's perception, knowledge, perceived barriers and stress.